2018
DOI: 10.14202/vetworld.2018.771-777
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Egyptian summer season on oxidative stress biomarkers and some physiological parameters in crossbred cows and Egyptian buffaloes

Abstract: Aim:The current study aimed to compare the impact of heat stress (HS) on some physiological functions and blood oxidative stress biomarkers between dry dairy crossbred (Balady X Friesian) cows and buffaloes during Egyptian summer season (July-September). Materials and Methods:A total of 26 healthy animals were equally used in the in the current study. The criterion for cows and buffaloes selection and the management conditions were similar. A total mixed ration to meet the animal's requirements was used, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
2
9
1
Order By: Relevance
“…The MDA concentration in transition and control buffaloes except in the three weeks postpartum were significantly higher (p<0.05) in summer compared to winter. The findings of Abdelrazek et al (2018) and Hady et al (2018) were similar to ours with significant increase in MDA postpartum compared to late gestation. Significantly higher levels of MDA on day zero of parturition reflected the increased oxidative stress in the animals.…”
Section: Biochemical Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…The MDA concentration in transition and control buffaloes except in the three weeks postpartum were significantly higher (p<0.05) in summer compared to winter. The findings of Abdelrazek et al (2018) and Hady et al (2018) were similar to ours with significant increase in MDA postpartum compared to late gestation. Significantly higher levels of MDA on day zero of parturition reflected the increased oxidative stress in the animals.…”
Section: Biochemical Parameterssupporting
confidence: 89%
“…Kumar et al (2011) also similarly observed significantly (p<0.05) increased erythrocyte SOD activity in buffaloes exposed to hot dry and hot humid conditions in a climate chamber. As the calving approached, the reserves of the antioxidant defence gets exhausted due to excessive lipolysis induced by persistently high cortisol levels and thereby excess generation of free radicals (Hady et al 2018). Hence parturition combined with seasonal stress significantly decreased the SOD levels to the day of calving which indicated that the combined effect was more pronounced on the day of calving.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…Insufficient LH pulse frequency impede the growth of follicles and decreases the ovulation chance and these conditions occurred due to lack of proper nutrition/ malnutrition (Ramoun et al 2012) and negative energy balance (Beever et al 2001). Moreover, high temperature and heat stress also had adverse effect on feed intake and consequently affect endocrine profiles and serum biochemical profiles (Hady et al 2018). Higher temperature-humidity index was also significantly affected TRBCs, Hb, ESR, T4, SOD, glutathione peroxidase (GSHPx), lipid peroxide (MDA) and TAC (Chaudhary et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…We further investigated the increased level of ROS in the MAC-T during heat treatment: the result suggests that heat induces oxidative stress in bovine mammary epithelial cells. A majority of the studies dealing with the effects of heat stress on oxidative stress biomarker response have been conducted in circumstances that sustained moderate to severe heat stress under strictly defined experimental conditions (environmentally controlled chambers) on selected high-yielding and intensively managed dairy cattle (Hady et al 2018). HO-1 is a corresponding oxidative stress marker and plays important roles in iron homeostasis, antioxidant defense, and antiapoptosis of cells (Loboda et al 2016).…”
Section: Discussionmentioning
confidence: 99%